Indonesia's perspective on Total Official Support for Sustainable Development (TOSSD) - Delalande, Guillaume (OECD Development Co-operation Working Papers, 2020)
This Working Paper presents the perspective of Indonesia on the concept of total official support for sustainable development (TOSSD), the extent of TOSSD resources provided by Indonesia and the capacity of the government to report on these resources. Indonesia broadly supported TOSSD as a relevant measure for monitoring SDG implementation and proposed some adjustments to the TOSSD methodology. Estimates for TOSSD provided by Indonesia in 2017 amount to USD 6 376 million, with USD 16 million for Pillar I (cross-border flows to other developing countries) and USD 6 360 million for Pillar II (contributions to international public goods). For Indonesia, activities recorded in TOSSD should not only be assessed in financial terms, but also in terms of their sustainable development impact. This pilot study attests to Indonesia's strong capacity to report on TOSSD Pillar I, but finds that tracking could be improved for a wider range of resources. The country also has the capacity to report on Pillar II.